Multi-doped bismuth ferrite thin films with enhanced multiferroic properties. Issue 10 (July 2019) - Xue, Mintao; Tan, Guoqiang; Xia, Ao; Chai, Zhengjun; Lv, Long; Ren, Huijun; Ren, Xixi; Li, Jincheng
Abstract: Thin films of multi-doped bismuth ferrite, Bi0.97−x Lax Sr0.03 Fe0·94 Mn0·04 Co0·02 O3 (BL x SFMC, x  = 0.00–0.18), are synthesized on a fluorine-doped tin oxide (FTO)/glass substrate. The structure and multiferroic properties of the film samples are characterized and tested. The results indicate that on doping, the structure of the BLx SFMC film changes has been changed. The concentrations of both oxygen vacancies and Fe 2+ are decreased. The BL0.18 SFMC thin film exhibits Ohmic conduction, which reduces the influence of the built-in electric field E bi of the space-charge region at the interface between an Au electrode and the BL x SFMC during polarization. The BL0.18 SFMC thin film also exhibits enhanced ferroelectric properties than the undoped film, with a higher residual polarization of 188 μC/cm 2 and a higher squareness ratio of 1.21. Meanwhile, the reduced number of oxygen vacancies also reduces the Fe 2+ /Fe 3+ ratio, thereby enhancing the Dzyaloshinskii–Moriya interaction of Fe–O–Fe bonds, and so the BL0.18 SFMC thin film exhibits enhanced ferromagnetism, with a saturation magnetization of M s  ≈ 3.94 emu/cm 3 . Thus, multi-ion doping can improve both the ferroelectric and ferromagnetic properties of BL x SFMC thin films.